Rickshaw Art: An Emblematic Visual Culture and Social Awareness Tool in Bangladesh - Sadia Afrin (Asiatic: IIUM Journal of English Language and Literature, 2023)
Rickshaw art is considered a significant part of visual culture in Bangladesh. It is not only a form of art, but also a medium for circulating messages among the common people about social, cultural, religious, ethical, philosophical, and national issues. Rickshaw painters and pullers act as campaigners for social awareness. This study seeks to investigate people’s thoughts about rickshaw art and its impact on society. It attempts to explain the images and messages painted on the back of rickshaws. Moreover, to illustrate the idea of this paper and evaluate the messages of rickshaw arts, multiple rickshaws from different cities in Bangladesh have been observed critically. Semi-structured interviews have been conducted to better comprehend the perspectives of rickshaw artists and rickshaw pullers. The major findings of the study suggest that rickshaws are very popular and that rickshaw art has changed substantially with the passage of time. Rickshaw artists possess some ideological and philosophical outlook for social transformation. In addition, the rickshaw pullers circulate the viewpoints of the painters in all corners of mega and small cities as well as villages in Bangladesh.